Rainfall-induced slope failures and preventive measures in Singapore - Harianto, Rahardjo (Nanyang Technological University and Housing & Development Board, 2016)
Steep residual soil slopes are generally characterized by a deep ground water table and a significant thickness of unsaturated soil above the water table. The negative pore-water pressure (matric suction) above the water table provides additional shear strength to the unsaturated soil. The unsaturated soil zone is also influenced by the ground surface moisture flux boundary condition changes (i.e. infiltration, evaporation and transpiration). As rain water infiltrates into slope, the matric suction in the soil decreases and as a result, the apparent shear strength associated with matric suction can decrease, causing the slope to become susceptible to failure. The factors which influence slope instability include the geology, topography of the area, soil types, soil properties, local climates (rainfall and evaporation) and water flow patterns within the slope. Generally, the effect of rainfall in inducing slope failures is attributed to the loss of matric suction as the wetting front advances from the ground surface or to the rise in the ground water table within the slope. It is also possible that both processes that occur simultaneously. Rainfall-induced slope failures are common in tropical areas such as Singapore that are covered by residual soils. These failures can pose potential danger to infrastructures and public safety. Therefore, a comprehensive study of the mechanisms associated with rainfall-induced slope failures, the stabilization, protection and repair works of failed slopes is needed. The Housing and Development Board (HDB) has partnered Nanyang Technological University (NTU) to undertake research studies with the objective of better understanding, and providing engineered solutions to rainfall-induced slope failure problems in HDB estates and to investigate the effectiveness of possible novel preventive measures. Unsaturated soil mechanics principles were incorporated into the research programs. The research methodolgy involved, firstly, the determination of relevant unsaturated soil properties together with field instrumentation and the monitoring of several slopes in Singapore. At the same time, computer modeling was undertaken to simulate seepage through unsaturated and saturated soil system in order to incorporate the effects of rainfall on slope stability.